Pelaksanaan Cyber Counseling di SMPN 59 Surabaya pada Masa Pandemi Covid-19 - Muchammad Syuhada'; Najlatun Naqiyah; Endang Pudjiastuti Sartinah (MODELING: Jurnal Program Studi PGMI, 2022)
The are many problems in online learning experienced by students and teacher consequence to Covid-19, presents its own challenges for guidance counseling teacher. Various efforts have been made by guidance and counseling teacher in order to help solve the problem faced by students during the pandemic through Cyber Counseling. This is the background for researchers to conduct e-counseling research conducted by guidance and counseling teacher. This study aims to describe the cyber counseling process carried out by guidance and counseling teachers during the Covid-19 pandemic. This research uses a qualitative approach and descriptive method. The location of this research in SMPN 59 Surabaya City with purposive sampling technique. Respondents in this research were homeroom teacher for grades VII, VIII, IX, two guidance and counseling teachers and students in grades VII, VIII, IX at SMPN 59 Surabaya. Research data obtained through observation, interviews and documentation. While the data analysis technique in this research is the Miles and Huberman (Interactive Model) The results of this research describe the Cyber Counseling method carried out by guidance and counseling teachers for students who have problems during the Covid-19 pandemic. Cyber Counseling can help solve problems faced by students during the Covid-19 pandemic. The advantage of Cyber Counseling is that it can be carried out anywhere and anytime. Meanwhile, the weakness of Cyber Counseling, if it is held for a long time and the application is heavy, it requires memory space and excess quota. However, this can be overcome with contributions from the school who facilitate handphone for those whose handphone do not support or because they are experiencing financial problems and provide free internet package quotas in order to support the implementation of Cyber Counseling.